The Challenge of Building a Scalable Postcapitalist Commons: The Limits of FairCoin as a Commons‐Based Cryptocurrency. Issue 3 (19th December 2020) - Dallyn, Sam; Frenzel, Fabian
Abstract: Postcapitalist commons are a growing area of interest in the efforts to generate alternatives to capitalism in the present. Commons are understood as self‐organised collectives based around shared resources; yet postcapitalist commons have an additional element, in operating within while projecting an "after" capitalism. This can give rise to tensions since commons striving for postcapitalism also require a certain amount of capital to survive and function within capitalism. FairCoop is a radical postcapitalist commons that adopted the cryptocurrency FairCoin in 2014. FairCoop, through FairCoin, was able to generate some trans‐local connections through its use of peer2peer technologies and was thus able to scale‐up. Its design, however, was ultimately unsustainable due to insufficiently clear boundaries from capital. After highlighting the lack of commons boundaries around FairCoop, we identify some additional commons‐capital boundary design principles which could contribute to the sustainability of future postcapitalist commons experiments that are seeking to scale.